The safety of asthma medications during pregnancy: an update for clinicians - Jennifer A. Namazy; Michael Schatz (Therapeutic Advances in Respiratory Disease, 2014)
Pregnancy may be complicated by new onset or preexisting asthma. This article reviews the recognition and management of asthma during pregnancy, as well as general principles of asthma medication use during pregnancy.